2011
DOI: 10.1111/j.1742-1241.2011.02794.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Catching the spike and tracking the flow’: Holter-temperature monitoring in patients admitted in a general internal medicine ward

Abstract: Temperature Holter monitoring reveals fever peaks that pass otherwise unobserved. Furthermore, chronobiological and complexity analysis of the temperature profile may provide quick and easy 'hidden information', not available to conventional care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 8 publications
(10 reference statements)
2
23
0
Order By: Relevance
“…Twelve studies examined the impact of continuous vital signs monitoring on clinical outcomes. Five of these were randomised controlled trials (Langhorne et al, 2010;Ochroch et al, 2006;Sulter et al, 2003;Tarassenko et al, 2005;Watkinson et al, 2006), one was a non-randomised controlled trial (Cavallini et al, 2003), three were controlled beforeand-after studies (Brown et al, 2014;Kisner et al, 2009;Taenzer et al, 2010) and three were prospective observational studies (Taenzer et al, 2014;Varela et al, 2011;Wan et al, 2004). All were single-centre studies.…”
Section: Impact Of Continuous Monitoring On Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies examined the impact of continuous vital signs monitoring on clinical outcomes. Five of these were randomised controlled trials (Langhorne et al, 2010;Ochroch et al, 2006;Sulter et al, 2003;Tarassenko et al, 2005;Watkinson et al, 2006), one was a non-randomised controlled trial (Cavallini et al, 2003), three were controlled beforeand-after studies (Brown et al, 2014;Kisner et al, 2009;Taenzer et al, 2010) and three were prospective observational studies (Taenzer et al, 2014;Varela et al, 2011;Wan et al, 2004). All were single-centre studies.…”
Section: Impact Of Continuous Monitoring On Clinical Outcomesmentioning
confidence: 99%
“…Six of the selected papers focussed on continuous measurement of a single vital sign parameter: five examined continuous pulse oximetry (CPOX) alone; (Kisner et al, 2009;Ochroch et al, 2006;Taenzer et al, 2010Taenzer et al, , 2014Wan et al, 2004) one study examined continuous temperature monitoring alone. (Varela et al, 2011) Taenzer et al and Wan et al compared intermittent oxygen saturation measurements with that collected by CPOX. (Taenzer et al, 2010(Taenzer et al, , 2014Wan et al, 2004) Taenzer reported that manually recorded data was significantly higher than those recorded by CPOX, and did not reflect the patients' physiological state.…”
Section: Impact Of Continuous Monitoring On Clinical Outcomesmentioning
confidence: 99%
“…Studies of CM were generally of medium duration, with six of the nine reviewed lasting between 6 and 23 months. Bias assessment of the nine CM studies identified potential validity and generalisability issues including cross-contamination where the same staff cared for intervention and control subjects (29); unblinded convenience sampling (31); selection of controls not directly comparable, for example from the two decades before the intervention (35); small sample sizes (28,42,44); or a small proportion (16%) of patients complying with CM for the anticipated observation period (31). In some cases, findings lost statistical significance after adjustment for potential confounders (40).…”
Section: Continuous Monitoringmentioning
confidence: 99%
“…Of the five CM studies assessing impact on early detection of deterioration (Table 2), four reported significantly positive improvements, while one study (31) found no change. Benefits were found through earlier identification of abnormal physiological signs (29,42), hypoxia (28) and fever (44).…”
Section: Fundingmentioning
confidence: 99%
“…This issue was studied in [6]. The two main findings of this study were that conventional temperature monitoring overlooks a significant proportion of fever peaks (the new method found a mean of 0.73 more peaks than low frequency readings), and, in addition, a high-frequency sampling of temperature such as the one proposed in this paper, may reveal some otherwise hidden characteristics of thermoregulation, such as differences between tuberculosis and HIV patients.…”
Section: Fever Peak Detectionmentioning
confidence: 81%